Effects of Intermittent Exposure to High Altitude on Blood Volume and Erythropoietic Activity - Schmidt, W. (High Altitude Medicine & Biology, 2002)
The purpose of this review is to describe changes in blood volume and erythropoietic activity occurring under different types of intermittent exposure to hypoxia. These hypoxic episodes can vary from a few seconds or minutes to hours, days, or even weeks. Short hypoxic episodes like sleep apnea only lead to a small increase in hemoglobin concentration, which is mainly due to a hormonal-mediated decrease in plasma volume. In most of these cases the cumulative time spent under hypoxia does not exceed the critical threshold of about 90 min. Endurance athletes and mountaineers who voluntarily expose themselves to hypoxia for some hours or during the night while spending the day at normoxia ("sleep high-train low" concept) do improve their physical performance. Despite raising erythropoietic activity, indicated by elevated plasma concentrations of EPO and the transferrin receptor, the postulated increase in red cell volume has not satisfactorily been proved. Frequent changes between low and high altitudes, which are usual in some South American and Asian countries, provoke similar adaptations in red cell mass as occur in high altitude residents. However, the plasma volume decreases at altitude and increases again when staying at sea level. Even after more than 20 yr of regular moving between low and high altitude, the total blood volume, hemoglobin concentration and hematocrit, as well as the plasma EPO concentration, noticeably oscillate during every hypoxic-normoxic cycle. We assume these changes to be an optimal rapid adaptation of the oxygen transport system to the prevailing hypoxic or normoxic environment. However, possible risks for the organism cannot be excluded.